Determination and multivariate statistical analysis of biochemical responses to environmental contaminants in feral freshwater fish Leuciscus cephalus, L - Machala, M; Dusek, L; Hilscherová, K; Kubínová, R; Jurajda, P; Neca, J; Ulrich, R; Gelnar, M; Studnicková, Z; Holoubek, I (Environmental toxicology and chemistry, 2001)
Modulations of 11 prospective biochemical markers of impacts of aquatic pollutants in liver tissue of chub (Leuciscus cephalus), caught at several sampling sites of a river with various pollution types and rates, were matched against analytical data of concentrations of organochlorine compounds, polycyclic aromatic hydrocarbons (PAHs), and heavy metals. Multivariate principal component analysis (PCA) of the field data showed general patterns of biochemical responses to different types of pollutants and relationships among the biomarkers. Cytochrome P4501A-dependent 7-ethoxyresorufin O-deethylase (EROD) activity, inducible by 2,3,7,8-tetrachlorodibenzo-p-dioxin and structurally related planar compounds, was strongly enhanced in the more contaminated areas. Compared with polychlorinated aromatic hydrocarbons, PAHs did not contribute so significantly to EROD induction. Testosterone 6 beta- and 16 alpha-hydroxylase activities, as an expression of the cytochrome P4503A27, were slightly increased at several sites but were significantly decreased in samples from some heavily polluted areas. Recently, these activities have been suggested as potential biomarkers of exposure to contaminants that do not induce cytochrome P4501A. In this study, their inhibition or induction was not associated with a specific class of monitored contaminants, and selectivities of these modulations are still to be investigated. Similar modulations of the prospective biochemical indicators of oxidative stress, including microsomal glutathione S-transferase activity, cytosolic glutathione S-transferase with ethacrynic acid, and glutathione reductase, were demonstrated by PCA. The pattern of the modulations of the microsomal nicotinamide adenine dinucleotide phosphate (NADPH)-dependent lipid peroxidation in vitro differed from the responses of the rest of oxidative stress parameters at some sampling sites. Further biochemical markers of oxidative stress under study, including in vivo lipid peroxidation, in vitro production of reactive oxygen species, and the concentration of metallothioneins did not correlate well with the concentrations of the contaminants. Principal component analysis demonstrated that the EROD activity, glutathione-dependent enzymes, and Fe(II)-enhanced lipid peroxidation formed a suitable battery of biomarkers of exposure.
Keywords: Liver; Animals; játra; chemické látky znečišťující vodu; multivariační analýza; Water Pollutants, Chemical; Multivariate Analysis; Polycyclic Compounds; Cyprinidae; Hydrocarbons, Chlorinated; Cytochrome P-450 CYP1A1; peroxidace lipidů; Lipid Peroxidation; Male; chlorované uhlovodíky; těžké kovy; cytochrom P-450 CYP1A1; Steroid 16-alpha-Hydroxylase; Enzyme Induction; enzymová indukce; steroid-16-alfa-hydroxylasa; polycyklické sloučeniny; zvířata; mužské pohlaví; Metals, Heavy